Psychosocial and Perceived Stress Associated with Pre-eclampsia in a Periurban Hospital - Tasnim, Saria; Choudhury, Shahida; Yesmin, Farida; Nazmeen, Summyia (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Pre-eclampsia complicates about 2% of pregnancy Exact aetiology of Pre-eclampsia is not known, however a number of psychosocial factors are often found to be associated with it. The purpose of the study was to ascertain the prevalence of psychosocial factors and perceived stress among patients with Pre-eclampsia. This was a cross sectional study done at institute of child and mother health during July to September, 2015. Total 71 women admitted for delivery with diagnosis of Preeclampsia were interviewed in the postnatal ward within three days of delivery using a structured questionnaire. Informed consent was taken. Data analyzed using SPSS version 22. Mean age was 23.9± 4.3 years with a range of 18-36 years, about a quarter were illiterate. Majority of them stay within extended family and mean household family member was 6.25± 1.93 about 77.5% of husbands were smokers, history of abortion was present in 21.1%. More than half of them have history of hypertension or diabetes in the family. Mean Systolic BP was 122.6±21.3 and mean diastolic BP was 83.5±14.6. About 42.2% reported that their family members were not aware of need of proper nutrition during pregnancy rather were indifferent. Ability to spend money by her was limited, sometimes by 33.8%, 28.2% if they ask for and 36.6% never have the opportunity. On recall of last one month period a significant proportion of women stated that they felt to be stressed sometimes during pregnancy. Risk factors for Preeclampsia like family history of Hypertension and Diabetes, passive smoking, low education level was found quite prevalent among women with pre-eclampsia. Majority of women reported to experience moderate stress and prevalence of stress was more among 19-24 years age group. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 119-126